Development and Validation of a Forensic Multiplex System With 38 X-InDel Loci - Chen, Ling; Pan, Xiyong; Wang, Yuan; Du, Weian; Wu, Weibin; Tang, Zhenya; Xiao, Cheng; Han, Xiaolong; Liu, Chao; Liu, Changhui (Frontiers in Genetics, 2021)
In the present study, a novel multiplex system, AGCU X-InDel 38 kit, was designed to amplify 38 X-InDel markers and Amelogenin in a single PCR. To demonstrate the suitability and efficiency for forensic applications, series of validation experiments were conducted, including sensitivity, species specificity, reproducibility, stability, case samples, balance of peak height, size precision, as well as allele frequency and forensic parameter analysis. The results showed that AGCU X-InDel 38 kit was capable to get full profiles even with 62.5 pg of template DNA, and full profiles can be obtained when hematin concentration ≤25 µmol/L or hemoglobin concentration ≤50 µmol/L, showing good tolerance to six common inhibitors. Moreover, the analyzed case samples indicated that AGCU X-InDel 38 kit had better performance for degraded and trace DNA samples. The 200 unrelated males from Guangdong Han population showed that the combined PDMale and PDFemale were both more than 0.999999999, and the combined MECKrüger, MECKishida and MECDesmarais Duo were 0.999369481, 0.999999917 and 0.999941556, respectively. Robust discrimination capability of this novel multiplex system could be demonstrated through the high values of forensic parameters. In conclusion, AGCU X-InDel 38 kit is sensitive, precise, reproducible and highly informative, and could be used as a complementary tool for complex and challenging kinship cases.